El nardo y la Sulamita en la unción de Maryam (Jn 12,1-8) - Luzarraga, Jesús (Gregorianum, 2002)
The cultural background of the nard and its mention in connection with the Sulamite in the Song of Songs (1,12) helps to understand Mary's gesture of anointing Jesus' feet (John 12,1-8). This was in thanksgiving for the resurrection. The nard as an exotic and strong aromatic plant acts mainly as a metaphor for life, love and value, confirmed by the symbolic values of the other plants mentioned with it in the Song (4,13s). Special reference is made to its presentation as pistikós and to its economic worth. John insists that the unction was performed on Jesus' feet; and this is the right way of anointing a man reclined for a banquet, while a previous anointing of the head remains plausible. The wiping up of the perfume on Mary's part hints to her participation in Jesus; both are defined by the significance of the nard. The nard was not used in any rite of kingship, nor for burial. And so Jesus' words referring to the poor and his burial are interpreted as an ironic reproach to Judas' criticism, and not as an explanation of Mary' gesture. The difficulty of combining the mention of some oil remaining for the future when all seems already poured out is solved by applying the narrative technique of presenting synchronicity and simultaneity.